Digital-age PAUD management innovations: Meeting children's needs through technology - Fahmi, Ade Ismail; Rosidin, Didin Nurul; Juanda, Anda; Karim, Abdul; Dewi, Maftuhah; Acharjya, Vasavvi (UIN Ar-Raniry Banda Aceh, 2025)
Management innovations in Early childhood education programs or the so called PAUD (Pendidikan Anak Usia Dini) management based on children's needs in the digital era have become very relevant for improving the quality of early childhood education. Technological developments provide opportunities for educational institutions to adapt learning methods that are more interactive and appropriate to children's developmental needs. This research explored the implementation of technology-based management innovations at PAUD Plamboyan 3, West Karawang, and evaluated their impact on children's learning and parental involvement. The study aims to determine the implementation of technology-based management innovations and to identify their effects on the learning process, parental involvement, and curriculum management. This research used a qualitative approach with a case study method. This qualitative research employs a case study method, with data collected through observations. The sample in this interview consisted of one school principal, five teachers, ten parents, and documents related to technology integration in learning. The research results show that using technology, such as learning applications and e-learning platforms, increases children's learning motivation and strengthens parental involvement in children's education. Curriculum management tailored to children's needs also supports children's cognitive, social, and motoric development. However, some parents need attention to challenges related to limited access to technology at home. This research is essential for the development of PAUD in the digital era by emphasizing the importance of teacher training, increasing access to technology, and the active role of parents in supporting children's learning process.